2022
DOI: 10.1111/jpc.16149
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of and potential risk factors for Developmental Language Disorder at 10 years in the Raine Study

Abstract: Aim This study sought to determine the prevalence of Developmental Language Disorder (DLD) in Australian school‐aged children and associated potential risk factors for DLD at 10 years. Methods This study used a cross‐sectional design to estimate the prevalence of DLD in Generation 2 of the prospective Raine Study. Participants included 1626 children aged 10 years with available language data. Primary outcomes included variables matching diagnostic criteria for DLD. Associations of other potential prenatal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…It is likely that the identification of being male as a risk factor is the result of retrospective reporting bias and referral bias in clinical samples, which has sex ratios ranging from 2:1 to 6:1 (WHO, 2019). Although there was some variability in sex distribution within the included studies, researchers who were stricter in their adherence to to established diagnostic criteria consistently reported that 53% of their low language sample were male (Calder et al, 2022;Norbury et al, 2016aNorbury et al, , 2016bOryadi-Zanjani et al, 2015). Therefore, it is important to reinforce the use of updated diagnostic criteria to mitigate the referral bias observed in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the identification of being male as a risk factor is the result of retrospective reporting bias and referral bias in clinical samples, which has sex ratios ranging from 2:1 to 6:1 (WHO, 2019). Although there was some variability in sex distribution within the included studies, researchers who were stricter in their adherence to to established diagnostic criteria consistently reported that 53% of their low language sample were male (Calder et al, 2022;Norbury et al, 2016aNorbury et al, , 2016bOryadi-Zanjani et al, 2015). Therefore, it is important to reinforce the use of updated diagnostic criteria to mitigate the referral bias observed in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Rudolph (2017) identified that children were equally as likely to meet criteria for Specific Language Impairment (SLI, now Developmental Language Disorder or DLD) if they were a ‘later talker’ as they would if their mother had low maternal education, they had a low 5‐min APGAR score, were born later or were male. Additionally, prospective cohort studies have identified risk factors for low language capacity beyond the preschool years such as parental education, socioeconomic disadvantage, non‐English speaking background, a family history of speech/language difficulties (Christensen et al., 2014; Reilly et al., 2018) and mothers smoking while pregnant (Armstrong et al., 2017; Calder et al., 2022). Most epidemiological studies have also failed to reveal sex‐related differences in language capacity, suggesting being a male may not be identified as a risk factor in unselected population samples (cf.…”
Section: Introductionmentioning
confidence: 99%
“…However, Tomblin et al found that once parental education was controlled for, the association was washed out, leading the authors to conclude that smoking is more likely a determinant of disadvantaged parenting environment than a causal risk factor for language disorder. Indeed, Calder et al (2022) highlighted that there was a significantly higher proportion of families who had household incomes < A$27,000 per year who did not provide language data, which made it difficult to rule out social determinants of DLD at 10 years. Another limitation noted in this study was that two important criteria for determining DLD diagnosis could not be obtained from the Raine Study dataset: (1) early onset of language difficulties; and (2) the functional impact of the condition.…”
Section: The Raine Studymentioning
confidence: 99%
“…Analysis of existing data was approved by the Raine Study and Curtin Human Research Ethics Committee (HREC approval number HRE2021-0117). Demographic information and the frequencies of children with (n = 104) and without (n = 1522) DLD are presented in Table 1, which is rereported from Calder et al (2022Calder et al ( , tab. 2, p. 2047.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation